Evaluation of Lesson Study on Lines and Angles - Ke Yan; Hui Deng; Zhouli Huang (Journal on Education, 2020)
The intersection of two lines was studied in grade 7, junior high school. This geometry material is very important, as the basic 3 dimensions that students will learn at the high school level. Exploring and persuading the two properties of vertical lines is the most difficult thing in teaching. Traditional teaching uses methods such as observation, drawing, measurement, and comparison to derive the properties of vertical lines, and expresses the properties of vertical lines in finer words, which easily create greater difficulty for students to understand. This research uses research and development methods, tries to use mathematical software to teach lines and angles and optimizes the basic concept of lines and angles. The results of this study provide specific references to the graphs and geometry of junior high school mathematics.